Peningkatan Literasi Teknologi Informasi Dan Komunikasi Siswa SMP Negeri 7 Tarakan Di Era Society 5.0 - Hanif, Kharis Hudaiby; Aris, Ibrahim; Prasetyo, Eko; Faqih, Radiansyah; fath, Aqil Miftahul; Sabtiandy, Dhandy (LPPM Universitas Harapan Bangsa Purwokerto, 2024)
Society 5.0 is characterized by the rapid and disruptive development of technology. This demands that each individual have the ability to use information and communication technology (ICT) wisely and responsibly. However, ICT also has negative impacts, such as addiction and misuse. Therefore, there is a need to improve ICT literacy from an early age. The purpose of this activity is to improve ICT literacy of students of SMP Negeri 7 Tarakan in the era of Society 5.0. This activity uses the methods of presenting materials, watching, practicing, and evaluating through written tests. The results of this activity are to grow the understanding and skills of ICT literacy of students of SMP Negeri 7 Tarakan so that they are ready to face the development of technology in the future.